2019
DOI: 10.3390/catal9110899
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Additives and Metals on Crystallization of Nano-Sized HZSM-5 Zeolite for Glycerol Aromatization

Abstract: Nano-sized HZSM-5 (n-HZSM-5) was synthesized and applied in the aromatization of glycerol. The effects of additives (carboxymethylcellulose sodium, NaCl, sodium alginate, etc.) on the chemical and physic properties of n-HZSM-5 during preparation were investigated. Metal modification was also investigated based on the synthesized n-HZSM-5. The results showed that the addition of carboxymethylcellulose sodium (CMC-Na), NaCl and sodium alginate (SA) led to forming smaller sizes of HZSM-5 and promoted the acid amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The NH 3 -TPD profile (Figure ) of the parent ZSM-5 indicates two intense peaks at 138 and 415 °C assigned to weak acid and strong acid sites, respectively . The SiO 2 /ZSM-5 sample showed a considerable decrease in both strong and weak acid peaks caused by the interaction of external silica species with the hydroxyl groups of the ZSM-5 support.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NH 3 -TPD profile (Figure ) of the parent ZSM-5 indicates two intense peaks at 138 and 415 °C assigned to weak acid and strong acid sites, respectively . The SiO 2 /ZSM-5 sample showed a considerable decrease in both strong and weak acid peaks caused by the interaction of external silica species with the hydroxyl groups of the ZSM-5 support.…”
Section: Resultsmentioning
confidence: 99%
“…The NH 3 -TPD profile (Figure 2) of the parent ZSM-5 indicates two intense peaks at 138 and 415 °C assigned to weak acid and strong acid sites, respectively. 28 The SiO 2 /ZSM- V total (cm 3 g −1 )…”
Section: ■ Introductionmentioning
confidence: 99%
“…Studies on the glycerol to aromatics synthesis revealed that protonated ZSM-5 (H-ZSM-5) has been effective for BTX and BTEX production due to its acidity and shape-selective characteristics [32]. The H-ZSM-5 contains sinusoidal channels (0.51 × 0.5 nm) that are crossed with straight channels of the dimension (0.53 × 0.56 nm) with intersection channel of 0.9 nm size [33,34]. However, the relatively large micropores of the catalysts limit the mass transport of large molecules and present a diffusion barrier, which ultimately results in undesired bulkier aromatics and cokes and eventual deactivation of the catalysts [35].…”
Section: Effect Of Hzsm-5 Acidity Metals Addition and Reaction Condit...mentioning
confidence: 99%
“…The mechanism proposed for this scenario posits that initially, coke is formed at the microporous channel of the H-ZSM-5 catalyst, followed by accumulation on the external surface of the zeolite as the time on stream increases [15]. The primary cause of the coke formation is the strong acid sites of the H-ZSM-5 catalysts, which have been improved by the design of shape-selective catalysts [35], metals, additive addition [33], and dealumination [43]. It is important to search for more binders that are capable of accumulating coke in amorphous form as opposed to the graphitic form, which is energy-intensive to regenerate.…”
Section: Prospects Of Catalytic Glycerol To Bio-aromaticsmentioning
confidence: 99%
“…The catalyst was placed in a fixed bed continuous flow reactor and glycerol was fed using H 2 as a carrier at a molar ratio of 15:1 (H 2 /glycerol). Two types of liquid products were produced: A hydrocarbon phase with aromatics and an aqueous phase with oxygenates [276]. The aromatic part might be considered as an alternative fuel or gasoline additive.…”
Section: Conversion Of Glycerol To Alkyl-aromatics (Gasoline)mentioning
confidence: 99%